A bibliometric analysis of biodiesel research during 1991 – 2015 - Zhang, Min (2020)
A bibliometric analysis based on the Science Citation Index Expanded (SCI-EXPANDED) from the Web of Science was carried out to provide insights into research activities and tendencies of the global biodiesel from 1991 to 2015. The document type and language, characteristics of publication outputs, Web of Science categories, journals, countries, institutions, author keyword and most cited articles were emphasized. The results indicated that annual output of the related scientific articles increased steadily. The top six categories focus on different aspects of biodiesel research. Bioresource Technology and Fuel were the two most frequent journals in the field of biodiesel research. The USA took a leading position and had the highest h-index (108) out of 122 countries/territories, followed by China and Brazil. Finally, author keywords and most cited articles were analyzed, indicating that microalgae, Jatropha curcas, vegetable oil and waste cooking oil are the most general raw materials for biodiesel production.